EFFECTIVENESS OF TRANSCUTANEOUS BILIRUBIN (TCBR) MEASUREMENT IN HIGH RISK NEONATES AND TO EVALUATE THE VALIDITY OF TRANSCUTANEOUS BILIRUBIN (TCBR) WITH TOTAL SERUM BILIRUBIN (TSBR) LEVELS IN BOTH LOW AND HIGH RISK NEONATES AT A TERTIARY CARE CENTER OF.... - Shahwar, Durre; Ariff, Sabina; Tariq, Batha; Rizvi, Arjumand; Rehan, Syed; Hussain, Ali Shabbir (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the utility of a Transcutaneous Bilirubin nomogram in high risk neonates and to evaluate the validity of Transcutaneous Bilirubin and Total serum bilirubin in both low and high-risk neonates.Study Design: Cross-sectional study.Place and Duration of Study: Postnatal Ward, Aga Khan University Hospital, Karachi, from May to Oct 2019.Methodology: The participants will include all neonates born and admitted in the well baby nursery withjaundice. All neonates with gestational age of